Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

Role of Indigenous and local knowledge in seasonal forecasts and climate adaptation: A case study of smallholder farmers in Chiredzi, Zimbabwe - Luckson Zvobgo; Peter Johnston; Oladapo M. Olagbegi; Nicholas P. Simpson; Christopher H. Trisos (Environmental Science & Policy, 2023)

The role of indigenous knowledge and local knowledge in water sector adaptation to climate change in Africa: a structured assessment - Luckson Zvobgo; Peter Johnston; Portia Adade Williams; Christopher H. Trisos; Nicholas P. Simpson (Sustainability Science, 2022)
Evidence is increasing of human responses to the impacts of climate change in Africa. However, understanding of the effectiveness of these responses for adaptation to climate change across the diversity of African contexts is still limited. Despite high reliance on indigenous knowledge (IK) and local knowledge (LK) for climate adaptation by African communities, potential of IK and LK to contribute to adaptation through reducing climate risk or supporting transformative adaptation responses is yet to be established. Here, we assess the influence of IK and LK for the implementation of water sector adaptation responses in Africa to better understand the relationship between responses to climate change and indigenous and local knowledge systems. Eighteen (18) water adaptation response types were identified from the academic literature through the Global Adaptation Mapping Initiative (GAMI) and intended nationally determined contributions (iNDCs) for selected African countries. Southern, West, and East Africa show relatively high evidence of the influence of IK and LK on the implementation of water adaptation responses, while North and Central Africa show lower evidence. At country level, Zimbabwe displays the highest evidence (77.8%) followed by Ghana (53.6%), Kenya (46.2%), and South Africa (31.3%). Irrigation, rainwater harvesting, water conservation, and ecosystem-based measures, mainly agroforestry, were the most implemented measures across Africa. These were mainly household and individual measures influenced by local and indigenous knowledge. Adaptation responses with IK and LK influence recorded higher evidence of risk reduction compared to responses without IK and LK. Analysis of iNDCs shows the most implemented water adaptation actions in academic literature are consistent with water sector adaptation targets set by most African governments. Yet only 10.4% of the African governments included IK and LK in adaptation planning in the iNDCs. This study recommends a coordinated approach to adaptation that integrates multiple knowledge sources, including IK and LK, to ensure sustainability of both current and potential water adaptation measures in Africa.

Climate Resilient Development Pathways in Global Drylands - Lindsay C. Stringer; Nicholas P. Simpson; E. Lisa F. Schipper; Siri H. Eriksen (Anthropocene Science, 2022)
The Intergovernmental Panel on Climate Change (IPCC) Working Group II Report on Adaptation, Impacts and Vulnerability identifies the urgent need to embark upon Climate Resilient Development Pathways. Climate Resilient Development acknowledges that adaptation needs to be undertaken together with mitigation and development, in joined-up, inclusive, just and equitable ways, across multiple arenas of engagement. In highly vulnerable systems with complex development contexts, such as drylands, where globally, warming is already exceeding that of humid areas, urgent action is vital, as the window of opportunity for Climate Resilient Development is rapidly closing. This paper considers challenges and opportunities in charting Climate Resilient Development Pathways in the world’s drylands. It highlights the importance of stakeholder engagement and partnership building to harness diverse knowledge sources, situating equity and justice concerns at the core of decision making and actions such as land restoration. It notes that while technological solutions offer potential to advance Climate Resilient Development, they need to be developed in an inclusive manner and used in ways that do not undermine Indigenous knowledge and local knowledge or exacerbate inequalities. Many of the challenges to Climate Resilient Development go beyond technology to include highly contextual differences in understanding, environment, institutions and access to finance. Adequate assessment of trade-offs in Climate Resilient Development actions in drylands remains vital to the framing of Climate Resilient Development Pathways for different groups. The paper concludes by identifying major urgent research gaps considering upscaling, stakeholder responsibilities and governance, the magnitude of investment that is necessary, and the need for appropriate monitoring, evaluation and learning.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The quorum‐sensing systems of Vibrio campbellii DS40M4 and BB120 are genetically and functionally distinct - Chelsea A. Simpson; Blake D. Petersen; Nicholas W. Haas; Logan J. Geyman; Aimee H. Lee; Ram Podicheti; Robert Pepin; Laura C. Brown; Douglas B. Rusch; Michael P. Manzella; Kai Papenfort; Julia C. van Kessel (Environmental Microbiology, 2021)
Summary Vibrio campbellii BB120 (previously classified as Vibrio harveyi ) is a fundamental model strain for studying quorum sensing in vibrios. A phylogenetic evaluation of sequenced Vibrio strains in Genbank revealed that BB120 is closely related to the environmental isolate V. campbellii DS40M4. We exploited DS40M4's competence for exogenous DNA uptake to rapidly generate greater than 30 isogenic strains with deletions of genes encoding BB120 quorum‐sensing system homologues. Our results show that the quorum‐sensing circuit of DS40M4 is distinct from BB120 in three ways: (i) DS40M4 does not produce an acyl homoserine lactone autoinducer but encodes an active orphan LuxN receptor, (ii) the quorum regulatory small RNAs (Qrrs) are not solely regulated by autoinducer signalling through the response regulator LuxO and (iii) the DS40M4 quorum‐sensing regulon is much smaller than BB120 (~100 genes vs. ~400 genes, respectively). Using comparative genomics to expand our understanding of quorum‐sensing circuit diversity, we observe that conservation of LuxM/LuxN proteins differs widely both between and within Vibrio species. These strains are also phenotypically distinct: DS40M4 exhibits stronger interbacterial cell killing, whereas BB120 forms more robust biofilms and is bioluminescent. These results underscore the need to examine wild isolates for a broader view of bacterial diversity in the marine ecosystem.

Evolving and Sustaining Ocean Best Practices and Standards for the Next Decade - Jay Pearlman; Mark Bushnell; Laurent Coppola; Johannes Karstensen; Pier Luigi Buttigieg; Francoise Pearlman; Pauline Simpson; Michele Barbier; Frank E. Muller-Karger; Cristian Munoz-Mas; Peter Pissierssens; Cyndy Chandler; et al. (Frontiers in Marine Science, 2019)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Statistical Power Calculations for Mixed Pharmacokinetic Study Designs Using a Population Approach - Frank Kloprogge; Julie A. Simpson; Nicholas P. J. Day; Nicholas J. White; Joel Tarning (The AAPS Journal, 2014)